Effects of Background Color on Stress-Linked Behavior in the Critically Endangered Lake Oku Clawed Frog (Xenopus longipes) - Arabella E. Graves; Jemma E. Dias; Christopher J. Michaels (Journal of Zoological and Botanical Gardens, 2023)
Ex situ amphibian populations are a key component of global amphibian conservation strategy, and optimal husbandry is vital to ex situ conservation success. Animal behavior can be used to inform captive welfare and improve husbandry practices. However, it has been little used for amphibians compared with mammals and birds. The goal of this study was to explore the effect of different colored tank backgrounds on the behavior of the critically endangered Lake Oku clawed frog (Xenopus longipes) in captivity. This was conducted by studying the behavior of a group of 24 captive frogs in 5 groups using established behavioral indicators of presumed stress. Resting and swimming behaviors, established in the literature as linked to acute stress, were recorded under conditions of three background colors and a standard husbandry control of no background. Frog groups were exposed to each background for five days with behavioral frequencies recorded daily from 11:00 until 13:00. Using generalized linear mixed models, we identified a significant effect of background days after the background was changed and the interaction between the two variables on both swimming and resting behavior. The results of this study suggest an initial response of stress to altering the background, modulated by the color of the background, followed by the extinction of the stress response such that by five days after the background change, behaviors were similar to the baseline and indistinguishable between treatments. Overall, this study suggests that frog stress behavior was not differentially directly affected by green, grey, black, or transparent backgrounds but that green and grey backgrounds were associated with the smallest stress response to background change. These colors may therefore be recommended to reduce the impact of stress from disturbance.